Mapping the potential of Kampung Balirejo to enhance local tourism destination initiation in Yogyakarta (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Diverse impacts characterise the implementation of the City without Slums (KOTAKU) program, significantly transforming Gajah Wong River into a thriving tourism village in Kampung Giwangan, Yogyakarta. Despite the potential of the Gajah Wong River embankment and KOTAKU infrastructure, Kampung Balirejo in Muja-Muju, which was conceptualised in 2021, had not achieved the full tourism potential. Therefore, this research aimed to formulate strategies for local tourism development by mapping the potential of Kampung Balirejo. The method used was qualitative descriptive design, including data collection through observation, interviews, and documentation, and SWOT analysis and mapping of attraction, activity, accessibility, amenity, accommodation, and ancillary services. The Prioritize Administrative elements included support from local government, private entities, management groups, and community capacity building. Based on the results, amenity, spatial arrangement, and attraction points were identified as essential factors for realising attraction and activity. Emphasising accessibility through bridge utilisation and bicycle route integration was also important. At the same time, accommodation was not a primary focus due to short-term visits. This research provided valuable information for sustainable tourism development in Kampung Balirejo to achieve an engaging and enduring destination.
Keywords: Initiation strategies; Local tourism destination; KOTAKU; Potential mapping; SWOT analysis